The Graying of Divorce: A Half Century of Change. (6th April 2022) - Brown, Susan L; Lin, I-Fen
Abstract: Objectives: We traced the historical arc of the rise in gray divorce (i.e., divorce that occurs among adults aged 50 and older) in the United States since 1970, elucidating unique patterns for middle-aged (aged 50–64) versus older (aged 65 and older) adults. Methods: Data from the 1970, 1980, and 1990 U.S. Vital Statistics Reports and the 2010 and 2019 American Community Survey (ACS) were used to chart the trends in gray divorce over the past half century. Drawing on the 2019 ACS, we estimated gray divorce rates across sociodemographic subgroups for today's middle-aged and older adults. We pooled the 2010 ( N = 757, 835) and 2019 ( N = 892, 714) ACS data to assess whether divorce risks are shifting for middle-aged versus older adults. Results: The gray divorce rate was low and grew only modestly between 1970 and 1990 before doubling by 2010. Since 2010, the rate has decreased slightly (but the decrease is not statistically significant). The gray divorce rate has stagnated among middle-aged adults but continues to climb among older adults. Discussion: Our study illustrates the graying of divorce over the past half century. Nowadays, 36% of U.S. adults getting divorced are aged 50 or older. The only age group with an increasing divorce rate is adults aged 65 and older, raising new questions about how they will navigate old age.